AKT and SGK kinases regulate cell migration by altering Scar/WAVE complex activation and Arp2/3 complex recruitment - Singh, Shashi Prakash; Paschke, Peggy; Tweedy, Luke; Insall, Robert H. (Frontiers in Molecular Biosciences, 2022)
Cell polarity and cell migration both depend on pseudopodia and lamellipodia formation. These are regulated by coordinated signaling acting through G-protein coupled receptors and kinases such as PKB/AKT and SGK, as well as the actin cytoskeletal machinery. Here we show that both Dictyostelium PKB and SGK kinases (encoded by pkbA and pkgB) are dispensable for chemotaxis towards folate. However, both are involved in the regulation of underlying cell motility. Cells lacking pkbA and pkgB showed a substantial drop in cell speed. Actin polymerization is perturbed in pkbA- and reduced in the protrusions of pkgB- and pkbA-/pkgB- mutants. The Scar/WAVE complex, key catalyst of pseudopod formation, is recruited normally to the fronts of all mutant cell types (pkbA-, pkgB- and pkbA-/pkgB-), but is unexpectedly unable to recruit the Arp2/3 complex in cells lacking SGK. Consequently, loss of SGK causes a near-complete loss of normal actin pseudopodia, though this can be rescued by overexpression of PKB. Hence both PKB and SGK are required for correct assembly of F-actin and recruitment of the Arp2/3 complex by the Scar/WAVE complex during pseudopodia formation.